2008
DOI: 10.1002/jbm.a.31907
|View full text |Cite
|
Sign up to set email alerts
|

Polymer surfaces structured with random or aligned electrospun nanofibers to promote the adhesion of blood platelets

Abstract: Fibrous membranes (nonwoven meshes) prepared via electrospinning technique have great potential in tissue engineering. This work is the first study on the behaviors of blood platelets at the nanostructured surface generated by electrospinning. Poly[acrylonitrile-co-(N-vinyl-2-pyrrolidone)] (PANCNVP) that shows excellent antiplatelet adhesion ability was directly electrospun onto its dense membrane surface. Polyacrylonitrile (PAN) samples were used as controls. The depth as well as the density of the nanofibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…The NF surfaces had higher surface FIB adsorption compared to PCL and NW surfaces resulting in higher platelet adhesion. This is consistent with recent work demonstrating higher platelet adhesion and activation on NF surfaces [67]. …”
Section: Resultssupporting
confidence: 94%
“…The NF surfaces had higher surface FIB adsorption compared to PCL and NW surfaces resulting in higher platelet adhesion. This is consistent with recent work demonstrating higher platelet adhesion and activation on NF surfaces [67]. …”
Section: Resultssupporting
confidence: 94%
“…Through results obtained from the images, it could be interpreted that nanostructured surfaces promoted the activation and adhesion of platelets. Wan and Xu in their study showed that the presence of nanofibers enhanced the activation and adhesion of platelets and induced the changes in surface topography and charge . Furthermore, SF‐coated Vit K/BC/CTS and PS/BC/CTS have more platelet attachment compared to other composite BC/CTS hemostatic dressings.…”
Section: Resultsmentioning
confidence: 97%
“…Wan and Xu in their study showed that the presence of nanofibers enhanced the activation and adhesion of platelets and induced the changes in surface topography and charge. 34 Furthermore, SF-coated Vit K/BC/CTS and PS/BC/CTS have more platelet attachment compared to other composite BC/CTS hemostatic dressings. Conversely, these groups showed less LDH activity compared to SF or SF/PC-coated BC/CTS dressings.…”
Section: Platelet Adhesionmentioning
confidence: 97%
“…To this end, electrospun nanofibrous scaffolds with various alignments (e.g. axially aligned, yarn, and radially aligned) have shown superior capacity in shaping cell morphology, guiding cell migration, and affecting cell differentiation when compared to other types of scaffolds both in vitro and in vivo 48,53,54 . More significantly, specific cellular behaviors (e.g.…”
Section: Biomimetic Nanofibrous Scaffolds For Tissue Engineeringmentioning
confidence: 99%